The Influence of Service Quality on Customer Satisfaction: Study in Blood Transfusion Service Units at RSCM - Budi Rahayu; Nafiah Ariyani; Levyda Levyda (Syntax Corporation Indonesia, 2023)
The best service quality is an important factor that must be owned by a company in order to be able to survive and still gain the trust of customers. Service quality is a performance indicator for health service providers such as hospitals. Hospitals will be more advanced if their performance can be maintained and improved according to patient demands. Therefore, hospital services must lead to market forces so that hospital orientation can retain customers so that the main goal can be carried out properly. Customer satisfaction is one of the determining factors and an indicator of quality and safety in UPTD RSCM. Customer satisfaction at UPTD RSCM is influenced by factors of reliability, responsiveness, assurance, empathy and tangible assets from the Blood Service Technician (TPD). The effect of service and performance of medical officers on customer satisfaction in the Blood Transfusion Unit of Dr. RSUPN. Cipto Mangunkusumo was carried out through the stages of research, namely: Analyzing the effect of service and performance of medical officers on patient satisfaction in the inpatient/or outpatient room at Dr. Cipto Mangunkusumo. From the results of data collection respondents, in this study the authors conclude a hypothesis; that customers are satisfied with the quality of service at the RSCM Blood Transfusion Unit on the factors of realibility, responsiveness, assurance, empathy and tangibles as a whole are at an index of 88.42% based on a Likert scale in the 'satisfied' category. The value of the consumer satisfaction index (CSI) lies in the 80% - 89.99% interval which indicates that the Customer Satisfaction Index is in the